2015
DOI: 10.1242/dev.127589
|View full text |Cite
|
Sign up to set email alerts
|

Modulating expression level of secreted Wnt3 influences cerebellum development in zebrafish transgenics

Abstract: The boundaries of brain regions are associated with the tissuespecific secretion of ligands from different signaling pathways. The dynamics of these ligands in vivo and the impact of its disruption remain largely unknown. Using light and fluorescence microscopy for the overall imaging of the specimen and fluorescence correlation spectroscopy (FCS) to determine Wnt3 dynamics, we demonstrated that Wnt3 regulates cerebellum development during embryogenesis using zebrafish wnt3 transgenics with either tissue-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 69 publications
6
26
0
Order By: Relevance
“…With the cytoneme-based transport mechanism, more cells adapted their final fate and hence the tissue established the proper proportions of the pattern much earlier in development than with the diffusion-based transport. For instance, 75% of all cells adopt their final fate after 55 minutes with the cytoneme-based transport, whereas the diffusive transport is almost two times slower in reaching this threshold (t = 80minutes), when choosing the diffusion constant to be D = 0.1 μm 2 /s similar to the measured value of Wnt3-GFP [ 55 ]. Even for a ligand which diffuses orders of a magnitude faster patterning occurs at a similar time point or later (cf.…”
Section: Resultsmentioning
confidence: 99%
“…With the cytoneme-based transport mechanism, more cells adapted their final fate and hence the tissue established the proper proportions of the pattern much earlier in development than with the diffusion-based transport. For instance, 75% of all cells adopt their final fate after 55 minutes with the cytoneme-based transport, whereas the diffusive transport is almost two times slower in reaching this threshold (t = 80minutes), when choosing the diffusion constant to be D = 0.1 μm 2 /s similar to the measured value of Wnt3-GFP [ 55 ]. Even for a ligand which diffuses orders of a magnitude faster patterning occurs at a similar time point or later (cf.…”
Section: Resultsmentioning
confidence: 99%
“…These transgenic lines were used as reporters of Wnt/β‐catenin signaling activity. Double transgenic embryos from in‐cross of Tg(‐4.0 wnt3 :Wnt3EGFP) F2 and Tg(‐4.0 wnt3 :Wnt3EGFP) F3 , which express functional fusion protein Wnt3‐EGFP in the brain, were screened to obtain appropriate Wnt3‐EGFP expression for SPIM‐FCS studies .…”
Section: Methodsmentioning
confidence: 99%
“…Our group showed that in zebrafish embryos, Wnt3 associates with domains on the membrane ( Azbazdar et al, 2019 ; Ng et al, 2016 ; Sezgin et al, 2017 ). Blocking the activity of Porc and thus reducing Wnt acylation resulted in reduced domain confinement and defective brain development in zebrafish embryos ( Ng et al, 2016 ; Teh et al, 2015 ). The understanding of the Wnt3 action mechanism in zebrafish brain development, therefore, requires identifying its source regions, determining its mode of transport, demarcating receiving target tissues, and measuring Wnt3-receptor interactions.…”
Section: Introductionmentioning
confidence: 99%